Plotinus on What We Think We Are - Stock, Wiebke-Marie (Classical Studies E-Books Online, Collection 2024., 2025)
The Neoplatonic philosopher Plotinus invites us to take part in his philosophizing when he encourages his readers to think about what they think they are, as living beings, human beings, as rational beings, ethical subjects and as philosophers. He is interested in what we say about ourselves in ordinary language and notices that such ordinary experience conflicts with what the Platonic tradition claims we (truly) are. This conflict does not lead him to turn away from the human terms and expressions, but impels him to take seriously what we say about ourselves and to explain it philosophically.